2020
DOI: 10.3390/molecules25235605
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine to Combat Novel Coronavirus (nCoV): Molecular Docking and Modeling to Cocrystallized Host Angiotensin-Converting Enzyme 2 (ACE2) and Viral Spike Protein

Abstract: Aims: Angiotensin-converting enzyme 2 (ACE2) plays an important role in the entry of coronaviruses into host cells. The current paper described how carnosine, a naturally occurring supplement, can be an effective drug candidate for coronavirus disease (COVID-19) on the basis of molecular docking and modeling to host ACE2 cocrystallized with nCoV spike protein. Methods: First, the starting point was ACE2 inhibitors and their structure–activity relationship (SAR). Next, chemical similarity (or diversity) and Pub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Our data show that even basal levels of the dipeptide are completely exhausted in COVID-19 patients. Saadah et al (15) predicted that COVID-19-induced oxidative stress would result in carnosine depletion. The protective effects of carnosine are widely attributed to its antioxidant, anti-glycation, and anti-inflammatory properties (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that even basal levels of the dipeptide are completely exhausted in COVID-19 patients. Saadah et al (15) predicted that COVID-19-induced oxidative stress would result in carnosine depletion. The protective effects of carnosine are widely attributed to its antioxidant, anti-glycation, and anti-inflammatory properties (10).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent papers suggest that carnosine may also protect against SARS-CoV-2 infection through more specific mechanisms. Molecular docking and modelling studies identified carnosine as the most promising drug candidate to prevent the binding of SARS-CoV-2 to the ACE2 receptor (15). Sustentacular cells of the olfactory system co-express the ACE2 receptor as well as TMPRSS2, a protease that facilitates viral entry, making these cells highly susceptible to SARS-CoV-2 (18).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has produced evidence suggesting that carnosine may act as an inhibitor of angiotensin-converting enzyme 2 (ACE2) which could then inhibit viral cellular entry via this protein. 36 Thus carnosine could suppress not only viral infection but also Covid-19-induced metabolic changes.…”
Section: Other Properties Of Carnosine Which May Help To Suppress Covid-19 Pathologymentioning
confidence: 98%
“…It has been proposed that the anti-oxidant and anti-glycating properties of carnosine may provide protection from this hypercoagulability, particularly in patients with altered glucose metabolism, who are known to have increased COVID-19 morbidity and mortality [ 16 , 17 ]. Others have suggested that carnosine may in fact prevent binding and internalization of SARS-CoV-2, potentially reducing both the incidence and severity of disease [ 20 ]. The SARS-CoV-2 spike protein has high binding affinity for angiotensin-converting enzyme 2 (ACE2), using this as a means of attachment and entry to the host cell [ 21 ].…”
mentioning
confidence: 99%
“…The SARS-CoV-2 spike protein has high binding affinity for angiotensin-converting enzyme 2 (ACE2), using this as a means of attachment and entry to the host cell [ 21 ]. In silico modelling of known pharmaceutical and therapeutic compounds revealed that carnosine is also able to bind to ACE2 as an inhibitor, potentially competing with the SARS-CoV-2 spike protein and reducing effective entry to host cells [ 20 ].…”
mentioning
confidence: 99%